Exact solution for an Ising model on the Cayley tree of order - Jamil, Hakim; Pah, Chin Hee (AIP Publishing, 2016)
We investigate an Ising model with two restricted competing interactions (nearest neighbors, and one-level neighbors) on the Cayley tree of order 5. The translation Gibbs measures is considered for this model. Our result of the critical curve shows that the phase transition occurs in this model, further it confirms a particular case of a conjecture